The Prevalence and Risk Factors of Residual Back Pain After Vertebroplasty for Osteoporotic Vertebral Compression Fractures: A Systematic Review and Meta‐Analysis - Li, Wenlong; Zhang, Bing; Mei, Chencheng; Li, Hui; Zhu, Ruizheng; Lin, Hao; Wen, Jianmin; Wu, Yang; Ma, Xianzhi (Orthopaedic surgery, 2025)
Osteoporotic vertebral compression fractures (OVCFs) are prevalent among the elderly. Percutaneous vertebroplasty (PVA) is a commonly adopted minimally invasive treatment, yet many patients endure residual back pain (RBP) posttreatment, affecting their recovery and quality of life. Given the inconsistent prevalence of RBP across studies and the multitude of influencing factors, a systematic review and meta-analysis is necessary to determine its prevalence and identify risk factors. English (PubMed, Embase, Web of Science, Ovid, Cochrane Library) and Chinese (CNKI, WanFang Data, VIP, CBM) literature databases were systematically searched until December 31, 2023. A random-effects meta-analysis was used to pool prevalence rates from individual studies. The associations between the identified risk factors and RBP were also analyzed. Sensitivity and subgroup analyzes were performed to identify the source of heterogeneity and to compare the prevalence estimates across the groups. The Joanna Briggs Institute's (JBIs) quality assessment checklist was used to evaluate the quality of the included studies. The I tests were used to assess heterogeneity among the studies. A total of 5146 articles were collected. Finally, 26 articles involving 9703 participants were included. Among them, 1245 experienced RBP. The prevalence of RBP in individual studies ranged from 4.56% to 50.00%, with a median of 14.90%. The pooled prevalence was 16.3% (95% CI: 13.5%-19.1%). The prevalence was higher among females [16.1% (95% CI: 13.1%-19.1%)] than males [15.9% (95% CI: 12.5%-19.2%)]. Subgroup analysis based on evaluation time showed that the prevalence was higher at 3 months or more after surgery [total: 17.3% (95% CI: 13.2%-21.4%) vs. 15.7% (95% CI: 12.1%-19.2%), males: 16.5% (95% CI: 12.3%-20.6%) vs. 15.3% (95% CI: 11.0%-19.6%), females: 16.9% (95% CI: 12.6%-21.1%) vs. 15.5% (95% CI: 11.6%-19.5%)]. Regarding the risk factors, several factors demonstrated significant associations with RBP. Patients with low pre-bone mineral density were more likely to experience RBP compared to those with higher density. Moreover, thoracolumbar fascia injury, unsatisfactory cement distribution, multiple vertebral fractures, and postoperative vertebral body height recovery rate were also identified as risk factors increasing the likelihood of RBP. RBP is common after PVA, indicating the imperative of intervention strategies to alleviate the suffering and reduce negative ramifications. Moreover, various risk factors should be comprehensively considered to accurately assess patients' conditions and formulate targeted treatment and rehabilitation plans to alleviate patients' RBP symptoms.